Analisis Pengaruh Arus Pengelasan Dan Jenis Elektroda Pada Struktur Mikro Material Baja Karbon Rendah - Darsono, Darsono; Hasbi, Muhammad; Aksar, Prinob (Teknik Mesin Universitas Halu Oleo, 2021)
The purpose of this study was to determine the changes in the microstructure that occur in low carbon steel due to welding using the type of electrodes E6013 and E7016 with a diameter of 2.6 with a current of 60-110. This research was carried out by several processes, namely specimen making, testing process and data analysis. In the specimen test, the microstructure of medium carbon steel was observed in the base metal region, the HAZ metal region, and the weld metal region. Microstructure testing was carried out to see the occurrence of changes in the microstructure of the specimen as a result of the welding process and the test results obtained were in the form of microstructure images with 500x magnification. The results showed that the changes in the microstructure that occurred in the HAZ region. This is found in the type of electrode E6013 indicating the higher the current used, the finer the grain size of the resulting structure. Meanwhile, for the E7016 electrode, it is the opposite where the higher the current used, the coarser the grain size of the resulting structure. Keywords: HAZ area, microstructure, type of electrode